FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA PADA MAHASISWA JURUSAN MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL–BANJARY BANJARMASIN - Periyadi peri; Sri Bulkia Sri Bulkia; Risnawati Risnawati (Jurnal Ilmu Ekonomi dan Bisnis, 2020)
: The main objective in this research is to study and analyze (1) How entrepreneurial factors consisting of social and family environment, innovation and creative, and technological environment influence the interest in entrepreneurship. (2) How does the social and family environment influence the interests of entrepreneurship. (3) How the influence of innovation and creativity on entrepreneurial interest. (4) How is the influence of the technological environment on entrepreneurial interest. The targets in this study include (1) the results of these researchers can be input for other researchers to conduct similar studies in the future. (2) Input materials can be used to enhance the development of student interest in entrepreneurship. (3) The results of this study are expected to be used as evaluations and useful information to make improvements oriented to the future, especially on students' interest in entrepreneurship. This research was conducted with quantitative methods and using analysis methods with SPSS Windows For Data as a data analysis tool.